2002
DOI: 10.1016/s1535-6108(02)00046-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor and Ink4a/Arf

Abstract: Ink4a/Arf inactivation and epidermal growth factor receptor (EGFR) activation are signature lesions in high-grade gliomas. How these mutations mediate the biological features of these tumors is poorly understood. Here, we demonstrate that combined loss of p16(INK4a) and p19(ARF), but not of p53, p16(INK4a), or p19(ARF), enables astrocyte dedifferentiation in response to EGFR activation. Moreover, transduction of Ink4a/Arf(-/-) neural stem cells (NSCs) or astrocytes with constitutively active EGFR induces a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
210
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 590 publications
(224 citation statements)
references
References 23 publications
13
210
1
Order By: Relevance
“…On the other hand, by interfering with MDM2 (mouse double minute 2)‐dependent degradation of p53, p14/p19 ARF controls p53/p21 WAF1 ‐induced G1 or G2 cell cycle arrest (Gil & Peters, 2006). Remarkably, using knockout mice models for this locus, it was possible to reveal that these senescence features could be associated with the terminal differentiation program in some specific cell types including keratinocytes (Paramio et al ., 2001; Bachoo et al ., 2002), chondrocytes (Philipot et al ., 2014), myofibers (Pajcini et al ., 2010), and also megakaryocytic cells (Muñoz‐Espín & Serrano, 2014). Megakaryocytic cells, myeloid‐derived immune cells from which blood platelets originate, are required for wound healing and immune responses (Besancenot et al ., 2010), opening new avenues to explore features of senescence in other types of immune cells.…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%
“…On the other hand, by interfering with MDM2 (mouse double minute 2)‐dependent degradation of p53, p14/p19 ARF controls p53/p21 WAF1 ‐induced G1 or G2 cell cycle arrest (Gil & Peters, 2006). Remarkably, using knockout mice models for this locus, it was possible to reveal that these senescence features could be associated with the terminal differentiation program in some specific cell types including keratinocytes (Paramio et al ., 2001; Bachoo et al ., 2002), chondrocytes (Philipot et al ., 2014), myofibers (Pajcini et al ., 2010), and also megakaryocytic cells (Muñoz‐Espín & Serrano, 2014). Megakaryocytic cells, myeloid‐derived immune cells from which blood platelets originate, are required for wound healing and immune responses (Besancenot et al ., 2010), opening new avenues to explore features of senescence in other types of immune cells.…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%
“…A strategy to circumvent some of the limitations of xenotranplantation while preserving the flexibility of transplant tumor model may involve the injection of genetically modified mouse cells, including lineage‐restricted stem/progenitor cells, orthotopically into syngeneic, immunocompetent mice (Bachoo et al., 2002; Heyer et al., 2010). This “mouse‐in‐mouse” transplant model has the advantage over human xenotransplant models to expose tumor development to the same immunological barriers that are present in GEMMs of cancer, albeit without the genetic heterogeneity that distinguishes otherwise apparently similar human tumors.…”
Section: Harnessing Mouse Models Of Cancer To Investigate Individualimentioning
confidence: 99%
“…Experiments with mature brain astrocytes have shown that combined loss of the tumor suppressor genes p16 Ink4 and p19 Arf and constitutive activation of the EGF receptor caused a loss of differentiation. These cells regained neural stem cell properties and formed glioblastomas when injected into mouse brains (Bachoo et al, 2002). Cancer stem cells can thus be derived both from normal stem cells and from more differentiated cells that are reprogrammed to express the properties of stem cells.…”
Section: Epigenetic Control Of Differentiation In Cancer Stem Cellsmentioning
confidence: 99%